A domestic use vertical farm unit for growing green vegetables and herbs - Kho, Yu Li (2017)
With the onset of climate change, temperatures and sea levels rising at alarming rates, vulnerable crops may lead to food insecurity. Therefore, more plants have to be grown to combat Global warming issues. In Singapore today, where more than 80% of the population lives in flats developed by Housing Development Board (HDB flats), this project explore the possibilities of integrating vertical farming in HDB flats. While there are existing commercial solutions to vertical farming available in the market, it provides the possibility of domestic usage. On a side note, genetically modified food are biological altered food that may pose human health risk (Disadvantages of Genetically Modified Food, 2010). With the increased availability of genetically modified food in supermarket, having a personal farm can ensure one’s well-being of eating organic food. However, due to the limited space available in Singapore, it is a challenge to own a large plot of land to grow and harvest enough food to feed a household. The proposed solution is to have the plants housed vertically, in order to allow more vegetables to be grown in the given space. The project consist of an investigation of the current commercial vertical farming and its plants growth indoors, where a comparison will be made between the two types of irrigation methods – Aeroponics or Hydroponics. In addition, material selection analysis will then be done to determine if there are any complications between the plants growth and the environment or vice versa. The mechanical properties of the material will also be investigated to determine the most suited for vertical farming. For example, the water absorptivity of certain material may affect compression properties and the challenge of housing the plants on a standalone structure. Thus, prototypes will be built and tested.